Beyondsoft IPO (A) - Jia, Ning, (SAGE knowledge. Cases., 2016)
One summer night in June 2009, Ben Wang, President of Beyondsoft Corporation, sat silently in the headquarter office in the High-tech Park of the Beijing Shangdi Information Industry Base. He was reconsidering the IPO plan which was interrupted by the global financial crisis of the previous year, after Beyondsoft had basically recovered from the crisis. Beyondsoft had spent five years for the IPO in the U.S. and built an overseas red chip structure as early as 2004. In 2007, however, when everything was ready and Beyondsoft was going to file an application with the U.S. Securities and Exchange Commission, a global financial crisis burst out. This case study examines this topic.